2021
DOI: 10.1186/s12885-021-09012-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the COVID-19 pandemic on psychological stress in breast cancer patients

Abstract: Background The majority of breast cancer patients are severely psychologically affected by breast cancer diagnosis and subsequent therapeutic procedures. The COVID-19 pandemic and associated restrictions on public life have additionally caused significant psychological distress for much of the population. It is therefore plausible that breast cancer patients might be particularly susceptible to the additional psychological stress caused by the pandemic, increasing suffering. In this study we th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 38 publications
4
33
0
Order By: Relevance
“…Our results align with other studies, such that Gebbia et al also reported dominant emotions such as fear, anger, and sadness [7]. Other studies note that women experienced worry and concern during the pandemic [22][23]25]. Women also reported emotional distress concerning changes to their BCC experiences [24].…”
Section: Discussionsupporting
confidence: 91%
“…Our results align with other studies, such that Gebbia et al also reported dominant emotions such as fear, anger, and sadness [7]. Other studies note that women experienced worry and concern during the pandemic [22][23]25]. Women also reported emotional distress concerning changes to their BCC experiences [24].…”
Section: Discussionsupporting
confidence: 91%
“…For example, health-related quality of life (HRQOL) questionnaires, Distress Thermometer, Hospital Anxiety and Depression Scale (HADS) and Perceived Stress Scale (PSS) were used in various studies [ 21 , 24 , 25 , 34 , 35 ] capturing disease-related distress that do not address the specific pandemic-related decisional dilemma. Other investigations addressed pandemic-related topics with a focus on risk perception [ 36 ]. Therefore, these results are only in part comparable.…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out in Germany, psychological stress was evaluated in patients with breast cancer during the health crisis, where palliative patients were the ones who had more complaints about the presence of fatigue, pain, and loss of appetite, interfering with their quality of life. 31 …”
Section: Discussionmentioning
confidence: 99%